Studi kasus: Pengaruh struktur kelompok terhadap kinerja anggota Senat Mahasiswa Fakutas Psikologi periode 2022-2023 - Ipaenin, Tiara Firgishanda (Maliki Interdisciplinary Journal, 2024)
The group structure has an influence on the performance of its members, the better the group structure is organized, the better the performance of the group members. A systematic group structure can bring hope for change and improve the performance of group members. This shows the importance of understanding group dynamics and effective collaboration in improving the performance of organizational members. With critical analysis, it is hoped that this article can provide a clear picture of the topic studied.